Pengaruh Pertumbuhan Produksi Sektor Primer dan Sektor Sekunder Terhadap Tingkat Kemiskinan Di Kabupaten Pacitan Tahun 2012-2019. - Ilham Maulana Putra Winandri; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2021)
This Study aims to find out the effect of production growth in primary and secondary sectors to poverty level in Pacitan during 2012-2019. The type of research is descriptive quantitative with regression techniques. The data is secondary data during 8 years that is 2012-2019. The results indicate that 1). The growth of primary production partially has no significant effect on poverty in Pacitan. 2). The growth of secondary production has negative effect on poverty, that every growth of secondary production reduces poverty level in Pacitan. 3). The growth of primary and secondary production simultaneously has significant effect to poverty level in Pacitan. 4). The coefficient of determination is 0.956 it shows that the effect of production growth on primary and secondary sectors are simultaneously 95.6% to poverty level in pacitan and 4.4% is affected by other variables out of the regression.